2009
DOI: 10.1071/rj08068
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on northern Australian rangeland livestock carrying capacity: a review of issues

Abstract: Grazing is a major land use in Australia’s rangelands. The ‘safe’ livestock carrying capacity (LCC) required to maintain resource condition is strongly dependent on climate. We reviewed: the approaches for quantifying LCC; current trends in climate and their effect on components of the grazing system; implications of the ‘best estimates’ of climate change projections for LCC; the agreement and disagreement between the current trends and projections; and the adequacy of current models of forage production in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(162 citation statements)
references
References 96 publications
9
148
0
5
Order By: Relevance
“…Already during the last decade, a high number of extreme heat waves affected major food crop growing by drought (Fischer, 2011; World Bank, 2012). McKeon et al (2009) observed that in Australia, current yearto-year variability exceeds projected changes in temperature and rainfall, but that climate change is projected to affect forage and animal production and ecosystem functioning.…”
Section: Climate Change and Livestock -A Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Already during the last decade, a high number of extreme heat waves affected major food crop growing by drought (Fischer, 2011; World Bank, 2012). McKeon et al (2009) observed that in Australia, current yearto-year variability exceeds projected changes in temperature and rainfall, but that climate change is projected to affect forage and animal production and ecosystem functioning.…”
Section: Climate Change and Livestock -A Literature Reviewmentioning
confidence: 99%
“…The models developed by Fischer (2011) assume full agronomic adaptation by farmers, whereas McKeon et al (2009) foresee challenges for important managerial and enterprise adaptations even in a developed country such as Australia. Vermeulen et al (2012) note that low-income producers will be more vulnerable to climate change owing to their limited ability to invest in adaptive institutions and technologies.…”
Section: Climate Change and Livestock -A Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Runoff water quality has also declined threatening key downstream ecosystems like the Great Barrier Reef lagoon (Furnas, 2003). With climate change projections of a hotter, drier and potentially more variable climate, sustainable management of northern Australian rangelands is likely to become even more challenging (McKeon et al, 2009). …”
Section: Introductionmentioning
confidence: 99%